Practical atlas for bacterial identification - Cullimore, D. Roy (CRC Press, 2010)
Begins by introducing the concept of bacteria community intelligence as reflected in corrosion, plugging, and shifts in the quality parameters in the product whether it be water, gas, oil, or even air. This book presents a fresh classification system for bacterial communities based upon their effect and activities, and not their composition